Single Prosecution System and the Effectiveness of the Attorney General's Office in Prosecuting Corruption Cases - Putri Villa Amilia; Indah Sri Utari (Universitas Negeri Semarang, 2026)
Corruption as an extraordinary crime requires special legal measures and law enforcement institutions with strong authority to ensure that the country's criminal policies are implemented in an integrated manner. This study aims to examine the urgency of strengthening the role of the Attorney General's Office as the sole coordinating body in the criminal justice system in order to reduce the challenges of dualism in prosecution between the Attorney General's Office and the Corruption Eradication Commission (KPK), which often leads to procedural inefficiencies and the phenomenon of back-and-forth file transfers. The research method used is normative juridical with a legislative and conceptual approach, using the Theory of Legal Effectiveness and Legal Certainty as the main analytical tools. Corruption as an extraordinary crime requires special legal measures and law enforcement institutions with strong authority to ensure that the country's criminal policies are implemented in an integrated manner. This study aims to examine the urgency of strengthening the role of the Attorney General's Office as the sole coordinating body in the criminal justice system in order to reduce the challenges of dualism in prosecution between the Attorney General's Office and the Corruption Eradication Commission (KPK), which often leads to procedural inefficiencies and the phenomenon of back-and-forth file transfers. The research method used is normative juridical with a legislative and conceptual approach, using the Theory of Legal Effectiveness and Legal Certainty as the main analytical tools. Corruption as an extraordinary crime requires special legal measures and law enforcement institutions with strong authority to ensure that the country's criminal policies are implemented in an integrated manner.